Vertikálne farmy - Kesanová, Michaela (Akademické nakladatelství CERM, 2013)
We perceive more intensively that forms of our settlement as well as our livelihood methods are functionally incompatible with the limited natural resources of planet Earth. The concept of vertical farms offers new insights into the possibilities for effective use of architecture creating a source of food in itself. It brings together the technology of cultivation without soil in a controlled environment of architecture. The greatest importance is in maximizing the surface using a vertical plane in the design of vertical farm, of which we are able to gather the harvest. Typologically, the most important element in the entity of vertical farm is a component of hydroponic cultivation. In terms of content there are two basic categories of vertical farms. Depending on the degree of food distribution, vertical farms can be attached to existing typologies or freestanding. Examination of a sample of projects shows three types of vertical farms, depending on the concentration of the various types of production and ancillary functions. The aim of the paper is to explore the special type of public buildings – vertical farms; to find suitable reference examples from all over the world by exploring the current state of surveyed problems; to choose the studied samples and those subjected to the chosen scientific method of exploration - evaluation of selected properties of studied samples by applying boundary conditions; to formulate recommendations / guidelines for the architectural design of vertical farms according to the results of the research. Architecture loses its meaning without the existence of people, and therefore should be interested in issues of food security. Effective utilization of the natural environment begins by managing our own existence and the environment that we create.

Príspevok pojednáva o aspektoch zavedenia poľnohospodárstva do identity architektúry ako o východisku pre dosiahnutie potravinovej sebestačnosti - jednej zo základných prvkov udržateľnosti. Schopnosť zabezpečiť si potravu predstavuje základnú podmienku pre prežitie ľudstva, a teda aj pre prežitie architektúry samotnej.
Vertical farms
Keywords: udržitelná architektura; potravinovou soběstačnost; veřejné budovy; vertikální farmy; hydroponie; sustainable architecture; food self-sufficiency; public buildings; vertical farm; hydroponics